Effects of Receiving Genetic Ancestry Results on Emerging Adults' Ethnic-Racial Identity Affirmation. Issue 4 (August 2021) - Williams, Chelsea D.; Smith, Tricia; Adkins, Amy; Walker, Chloe J.; Santana, Arlenis; Lozada, Fantasy T.; Su, Jinni; Dick, Danielle M.
Ethnic-racial identity (ERI) is associated with adaptive outcomes in emerging adulthood, but more research is needed on factors that may inform ERI, such as receiving one's genetic ancestry results. The current study examined changes in ERI using a pre-test post-test design in which 116 emerging adults 18–25 years were randomly assigned to either receiving their genetic ancestry results before the post-test (the testing condition) or after post-test (the control condition). We also tested whether ethnicity/race and gender moderated these associations. Findings indicated that male students of color (SOC) in the testing condition experienced an increase in ERI affirmation from pre-test to post-test, and male SOC in the control condition experienced a decrease in ERI affirmation from pre-test to post-test. There were no significant differences in ERI affirmation change between students in the testing condition and control condition for female SOC, White males, or White females.